Maternal Age and Stage of Pregnancy as Determinants of UTI in Pregnancy: A Case of Tamale, Ghana - Jacob Loonin Laari; Martin Anab; Damyetin Peter Jabong; Kasim Abdulai; Abdul Rauf Alhassan (Hindawi Limited, 2022)
Introduction. Urinary tract infection (UTI) is the world's second most common cause of death, trailing only respiratory tract infections. Because of anatomical and physiological changes along the urinary tract, pregnant women accounted for approximately 20% of all cases of urinary tract infection. Aim. This study sought to assess maternal age and stage of pregnancy as determinants of UTI among pregnant women in Tamale. Methods. This study employed a descriptive cross-sectional survey as the study design in the antenatal clinic of Tamale Central Hospital (TCH). This was carried out by reviewing laboratory records of urinalysis results done on pregnant women. Data entry and analysis were performed by the Statistical Package for the Social Sciences (SPSS) version 20. Chi-square and binary logistics analysis were used to determine the relationship. Results. Data analysis was done for 158 pregnant women, most (35.4%) were within the age group of 36-45 years, and most (38.6%) were within their first trimester. The overall prevalence of UTI infections among pregnant women was 33.5%. The prevalence was 27.8% for candiduria and 8.9% for bacteriuria. Women in the first trimester of their pregnancy were more likely to have UTI (AOR=2.48, 95% CI =1.03-5.94). Also, Pregnant women of the age group of 26-35 years were less likely to get UTIs as compared to those of the age group 15-25 years (AOR=0.40, 95% CI =0.17-0.92). Finally, those of the age group of 36-45 years were less likely to get UTI as compared to those of the age group 15-25 years (AOR=0.28, 95% CI =0.12-0.66). Conclusion. The prevalence of UTI among studied pregnant women was high (38.0%), and the most prone maternal age group and trimesters to UTI are 15-25 years and first trimester, respectively.